Comment choisir son prêtre ? Modalités d’attribution et conditions d’exercice des prêtrises royales à l’époque hellénistique = How to Choose Your Priest? Modalities of Appointment and Conditions of Tenure of Royal Priesthoods in the Hellenistic Period - Julien, Dechevez (Mythos, 2025)
With the exception of the eponymous priesthoods of dynastic cults, the royal priesthoods of the Hellenistic period have been scarcely explored in modern research. Moreover, they have often been the subject of hasty generalizations, which have led to their systematic interpretation as positions of power involving close relationships with ruling authorities. This contribution aims to reassess the nature of these functions by examining the different modes of appointment of royal priesthoods and the type of missions of their officiants. The analysis of the perquisites and obligations linked to the tenure of a royal priesthood also sheds light on the integration of royal honors into the pantheons of Greek cities, from the perspective of the individuals who serve these cults.